Iron-catalyzed C–N bond formation via oxidative Csp3–H bond functionalization adjacent to nitrogen in amides and anilines: Synthesis of N-alkyl and N-benzyl azoles. Issue 28 (8th July 2015) - Saidulu, G.; Kumar, R. Arun; Reddy, K. Rajender
Graphical abstract: Abstract: Iron catalyzed oxidative protocol was developed to couple azoles with amides to generate N -alkylazole derivatives in moderate to excellent yields using tertiarybutyl hydroperoxide as an oxidant under mild reaction conditions. Furthermore, this protocol explored to couple azoles with N -alkylanilines, unexpectedly N -benzyl azoles were obtained as major products under these oxidative conditions.